2000
DOI: 10.1136/jnnp.69.4.550
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in young patients with Parkinson's disease: a population based comparison with healthy controls

Abstract: Answers from a multiple choice questionnaire on the opinions about public sexual attitudes, on emotion from personal sexual practice, on personal sexual function, and on general health perception were compared between 121 patients with Parkinson's disease (mean age 45 years) and 126 age and sex matched community derived controls. Patients were more dissatisfied with their present sexual functioning and relationship, and perceived their general health as poorer than the controls, whereas opinions about public s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 12 publications
3
28
0
5
Order By: Relevance
“…The reported prevalence of sexual symptoms ranges from 37 to 65% [66,67,68]. In the present study, sexual dysfunction was recorded in more than half of the patients (66.6%).…”
Section: Discussionmentioning
confidence: 54%
“…The reported prevalence of sexual symptoms ranges from 37 to 65% [66,67,68]. In the present study, sexual dysfunction was recorded in more than half of the patients (66.6%).…”
Section: Discussionmentioning
confidence: 54%
“…While the greater prevalence of SD in PD patients, when compared with age-matched healthy controls, is not controversial, it is not clear whether the known brain 'lesions' related to PD (supposedly relevant for maintaining normal sexual function) have a decisive impact on the prevalence of SD in PD [Celikel et al 2008;Sakakibara et al 2001;Jacobs et al 2000;Welch et al 1997]. An often-cited study found no greater prevalence of SD in married male PD patients, when compared with matched patients with another chronic, but nonneurologic, disease (arthritis) [Lipe et al 1990].…”
Section: Introductionmentioning
confidence: 99%
“…SD is common in patients with PD [Hand et al 2010;Celikel et al 2008;Bronner et al 2004;Jacobs et al 2000;Zesiewicz et al 2000;Welch et al 1997;Wermuth and Stenager, 1995;Brown et al 1990;Koller et al 1990], associated with depression and relationship dissatisfaction [Wielinski et al 2010]. SD has been reported as common even in young patients with PD (mean age 49.6 years).…”
Section: Introductionmentioning
confidence: 99%
“…Die geringe Anzahl von Untersuchungen zu diesem Problemfeld mag darin begründet liegen, dass die meisten an Morbus Parkinson erkrankten Patienten sich bereits in einer Lebensphase befinden, in der sich dieses Thema im soziokulturellen Kontext möglicherweise als weniger vorrangig darstellt. Ob sich dabei die Sexualität von Parkinson-Patienten von gesunden Altersgenossen überhaupt unterscheidet, ist aufgrund eingeschränkter Studienbedingungen bis heute nicht völlig geklärt, da entweder nur weibliche oder männli-che Patienten eingeschlossen wurden oder die Vergleichsgruppe aus den jeweiligen Lebenspartnern bestand [11].…”
Section: Sexualität Und M Parkinsonunclassified
“…Allgemeine Unzufriedenheit mit der eigenen sexuellen Aktivität und Funktion im Vergleich mit der Zeit vor Erkrankungsbeginn wird in einer Reihe von Studien berichtet [11,14,16]. Brown Eine alters-und geschlechtsangepasste Vergleichsstudie an 121 jüngeren Parkinson-Patienten (mittleres Alter 45 Jahre) konnte eine gesteigerte Unzufriedenheit mit ihren sexuellen Funktionen bei dieser Patientengruppe bestäti-gen, ohne dass tatsächlich signifikant mehr sexuelle Funktionsstörungen vorgelegen hätten [11].…”
Section: Sexualität Und M Parkinsonunclassified